2011
DOI: 10.4049/jimmunol.1101503
|View full text |Cite
|
Sign up to set email alerts
|

The TLR3/TICAM-1 Pathway Is Mandatory for Innate Immune Responses to Poliovirus Infection

Abstract: Cytoplasmic and endosomal RNA sensors recognize RNA virus infection and signals to protect host cells by inducing type I IFN. The cytoplasmic RNA sensors, retinoic acid inducible gene I/melanoma differentiation-associated gene 5, actually play pivotal roles in sensing virus replication. IFN-β promoter stimulator-1 (IPS-1) is their common adaptor for IFN-inducing signaling. Toll/IL-1R homology domain-containing adaptor molecule 1 (TICAM-1), also known as TRIF, is the adaptor for TLR3 that recognizes viral dsRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
71
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 54 publications
0
71
0
Order By: Relevance
“…MDA-5 is generally thought to detect picornaviruses (48)(49)(50). However, evidence suggests a pivotal role for TLR3 and RIG-I as well (51)(52)(53)(54)(55). We recently reported that EV-D68 perturbs TLR3 via proteolytic cleavage of the TIR-domain-containing adapterinducing interferon-␤ (TRIF) adaptor (35).…”
Section: Discussionmentioning
confidence: 99%
“…MDA-5 is generally thought to detect picornaviruses (48)(49)(50). However, evidence suggests a pivotal role for TLR3 and RIG-I as well (51)(52)(53)(54)(55). We recently reported that EV-D68 perturbs TLR3 via proteolytic cleavage of the TIR-domain-containing adapterinducing interferon-␤ (TRIF) adaptor (35).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of PV infection, TLR3-mediated type I IFN production is important for viral clearance in vivo 15,16 . In vitro PV infection of splenic DCs promotes type I IFN production in a TLR3-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…TLR3-or TICAM-1-deficient human PV receptor (PVR)-transgenic mice were more susceptible than normal PVR-transgenic mice to intraperitoneal or intravenous inoculation with a low titre of PV 15,16 . TLR3-dependent type I IFN production by splenic CD11c þ DCs and macrophages was essential for the protection of PVR-transgenic mice against PV infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although TLR3/TICAM-1 participate in BMDC maturation in response to cell-derived virus RNA in RNA virus infections (Ebihara et al, 2008;Oshiumi et al, 2011), this is not the case in MV infection. , 2013).…”
Section: Discussionmentioning
confidence: 99%